Heresy, forgery, novelty: condemning, denying, and asserting innovation in ancient Judaism - Klawans, Jonathan (Oxford University Press, 2019)
Heresies, forgeries, novelties -- Heresy without orthodoxy: Josephus and the rabbis on dangerous beliefs -- Secret supersessionism? Intimations of novelty concealed at Qumran -- Innovation asserted: the novelties of early Christianity.